Resin composition
A resin composition combining flat and spherical magnetic powders addresses dispersion issues, enhancing magnetic permeability and processing ease for uniform films and pastes.
Patent Information
- Application Number
- JP2021017356
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-05
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-02-05
AI Technical Summary
Existing resin compositions containing flat magnetic powder face challenges in uniform dispersion, leading to difficulties in forming smooth films and achieving high magnetic permeability.
A resin composition combining flat and spherical magnetic powders, with specific size and oblateness ratios, is used to enhance dispersion and magnetic permeability, facilitating easy formation into pastes and films.
The composition achieves excellent relative magnetic permeability and ease of processing, enabling the production of uniform films and pastes with improved magnetic properties.
Smart Images

Figure 0007604926000002 
Figure 0007604926000003 
Figure 0007604926000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition containing a magnetic powder, and further to a cured product, a resin sheet, a circuit board, and an inductor board obtained by using the resin composition. [Background technology]
[0002] As electronic devices have become smaller and thinner in recent years, there is an increasing demand for printed wiring boards and the inductor components (coils) mounted on them to be smaller and thinner as well. When inductor components are mounted as chip components, there is a limit to how thin the printed wiring board can be made.
[0003] In response to this, for example, a method is known in which an inductor is formed in an inner layer of a printed wiring board by forming a magnetic layer on a printed circuit board using a resin sheet containing magnetic powder in a resin composition layer (Patent Document 1). Also, for example, a method is known in which a magnetic layer is formed by screen printing a paste material containing magnetic powder on a board including wiring (Patent Document 2).
[0004] In these embodiments, from the viewpoints of suppressing magnetic loss as low as possible and of viscosity, elastic modulus, etc., spherical magnetic powder has been preferably used.
[0005] On the other hand, in response to the demand for higher performance inductors, pastes and films containing magnetic powder are also required to have higher magnetic permeability. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2018 / 194099 [Patent Document 2] JP 2020-087939 A Summary of the Invention [Problem to be solved by the invention]
[0007] Although it is conceivable to use flat magnetic powder to increase magnetic permeability, there is a problem that flat magnetic powder is difficult to disperse in resin, and it is difficult to obtain a paste-like resin composition in which the magnetic powder is uniformly dispersed. In addition, when a resin composition containing flat magnetic powder is applied to form a film, there is a problem that it is difficult to produce a uniform film, as many small holes are generated on the film surface.
[0008] An object of the present invention is to provide a resin composition which can be easily formed into a paste or a film and which can provide a magnetic material having excellent relative magnetic permeability. [Means for solving the problem]
[0009] As a result of intensive research to achieve the above-mentioned object, the inventors unexpectedly discovered that when specific (A-1) flat magnetic powder and (A-2) spherical magnetic powder are used together, it is possible to easily form the powder into a paste or a film, and also to achieve excellent relative permeability, thereby completing the present invention.
[0010] That is, the present invention includes the following. [1] A resin composition comprising (A) a magnetic powder and (B) a thermosetting resin, The component (A) contains (A-1) flat magnetic powder and (A-2) spherical magnetic powder, A resin composition, in which the average minor axis length of the component (A-1) is 1 μm or more. [2] The resin composition according to the above [1], wherein the aspect ratio of the component (A-1) is 2 or more, and the aspect ratio of the component (A-2) is less than 2. [3] The resin composition according to the above [1] or [2], wherein the average particle size of the component (A-1) is 10 μm to 100 μm. [4] The resin composition according to any one of the above [1] to [3], wherein the average particle size of the component (A-2) is 0.1 μm to 40 μm. [5] The resin composition according to any one of the above [1] to [4], wherein a mass ratio of the component (A-1) to the component (A-2) (component (A-1) / component (A-2)) is 0.4 to 2.3. [6] The resin composition according to any one of the above [1] to [5], wherein the content of the component (A) is 25 vol % to 75 vol % when the non-volatile components in the resin composition are taken as 100 vol %. [7] The resin composition according to any one of the above [1] to [6], wherein the content of the component (A) is 70% by mass to 96% by mass, based on 100% by mass of the non-volatile components in the resin composition. [8] The resin composition according to any one of the above [1] to [7], wherein the component (B) contains an epoxy resin (B-1). [9] The resin composition according to any one of the above [1] to [8], further comprising (C) a curing accelerator.
[10] The resin composition according to any one of the above [1] to [9], wherein a cured product of the resin composition has a relative permeability (μ') of 11 or more when measured at a measurement frequency of 10 MHz and 23°C.
[11] The resin composition according to any one of the above [1] to
[10] , having a viscosity at 25°C of 0.05 Pa·s to 1500 Pa·s.
[12] A resin sheet comprising a support and a resin composition layer formed on the support from the resin composition according to any one of [1] to
[11] above.
[13] A cured product of the resin composition according to any one of [1] to
[11] above.
[14] A circuit board comprising: a substrate having a through-hole; and a cured product of the resin composition according to any one of [1] to
[11] above filled in the through-hole.
[15] A circuit board comprising a cured layer which is a cured product of the resin composition according to any one of the above [1] to
[11] .
[16] An inductor substrate comprising the circuit substrate according to
[14] or
[15] above. Effect of the Invention
[0011] According to the resin composition of the present invention, it is possible to obtain a magnetic material which can be easily formed into a paste or a film and has excellent relative magnetic permeability. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view of a core substrate as an example of a method for manufacturing a circuit board according to a first embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a core substrate in which a through hole is formed, as an example of the method for manufacturing the circuit board according to the first embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing a state of a core board in which a plating layer has been formed in a through-hole as an example of the method for manufacturing a circuit board according to the first embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view showing a state of a core board in which a resin composition has been filled into through-holes as an example of the method for producing a circuit board according to the first embodiment. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing the state of the core substrate after the filled resin composition has been thermally cured, as an example of the method for producing the circuit board of the first embodiment. [Figure 6] FIG. 6 is a schematic cross-sectional view showing the state of the core substrate after polishing the cured product as an example of the method for producing the circuit board according to the first embodiment. [Figure 7] FIG. 7 is a schematic cross-sectional view showing a state of a core substrate with a conductor layer formed on a polished surface thereof as an example of the method for manufacturing a circuit board according to the first embodiment. [Figure 8] FIG. 8 is a schematic cross-sectional view showing the state of a core substrate on which a pattern conductor layer is formed as an example of the method for manufacturing a circuit board according to the first embodiment. [Figure 9] FIG. 9 is a schematic cross-sectional view for illustrating step (A) included in an example of the method for producing the circuit board according to the second embodiment. [Figure 10] FIG. 10 is a schematic cross-sectional view for illustrating step (A) included in an example of the method for producing the circuit board according to the second embodiment. [Figure 11] FIG. 11 is a schematic cross-sectional view for explaining step (B) included in the example of the method for manufacturing the circuit board according to the second embodiment. [Figure 12]FIG. 12 is a schematic cross-sectional view for explaining step (D) included in the example of the method for producing the circuit board according to the second embodiment. [Figure 13] FIG. 13 is a schematic plan view of an inductor component including a circuit board obtained by the circuit board manufacturing method according to the second embodiment, as an example, viewed from one side in the thickness direction. [Figure 14] FIG. 14 is a schematic diagram showing a cut end surface of an inductor component including a circuit board obtained by the manufacturing method for a circuit board of the second embodiment, cut at the position indicated by the dashed line II-II in FIG. 13 as an example. [Figure 15] FIG. 15 is a schematic plan view illustrating the configuration of a first conductor layer in an inductor component including a circuit board obtained by the method for manufacturing a circuit board according to the second embodiment, as an example. [Figure 16] FIG. 16 is a schematic diagram of a magnetic powder particle for explaining the relationship between the thickness, minor axis length, and major axis length of the magnetic powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0014] <Resin composition> The resin composition of the present invention includes (A) a magnetic powder and (B) a thermosetting resin, the magnetic powder (A) includes (A-1) a flat magnetic powder and (A-2) a spherical magnetic powder, and the average minor axis length of the flat magnetic powder (A-1) is 1 μm or more. By using such a resin composition, a magnetic material that is easy to form into a paste or a film and has excellent relative magnetic permeability can be obtained.
[0015] The resin composition of the present invention may further contain optional components in addition to (A) magnetic powder and (B) thermosetting resin. Examples of the optional components include (C) curing accelerator, (D) thermoplastic resin, (E) dispersant, (F) other additives, and (G) organic solvent. Each component contained in the resin composition will be described in detail below.
[0016] <(A) Magnetic powder> The resin composition of the present invention contains (A) a magnetic powder. The (A) magnetic powder can impart magnetism to the resin composition. The (A) magnetic powder is contained in the resin composition of the present invention in the form of particles. In the resin composition of the present invention, the (A) magnetic powder contains both (A-1) a flat magnetic powder and (A-2) a spherical magnetic powder.
[0017] <(A-1) Flat magnetic powder> In the resin composition of the present invention, the magnetic powder (A) includes a flat magnetic powder (A-1). The flat magnetic powder (A-1) may be used alone or in combination of two or more kinds.
[0018] The flat magnetic powder (A-1) may be either a soft magnetic powder or a hard magnetic powder, but in one embodiment, from the viewpoint of obtaining the effects of the present invention significantly, it is preferable that it is a soft magnetic powder. The flat magnetic powder (A-1) may be, for example, a magnetic metal powder, a magnetic metal oxide powder, or the like.
[0019] Examples of the magnetic metal oxide powder include ferrite powder and iron oxide powder.
[0020] The ferrite powder may be either a hard ferrite powder or a soft ferrite powder, but in one embodiment, from the viewpoint of increasing the relative magnetic permeability, it is preferable that the ferrite powder is a soft ferrite powder. The ferrite powder may be either a spinel ferrite powder, a hexagonal ferrite powder, or a garnet ferrite powder, but in one embodiment, it is preferable that the ferrite powder is a spinel ferrite powder, from the viewpoint of increasing the relative magnetic permeability. The ferrite powder may be a single crystal ferrite powder or a polycrystalline ferrite powder.
[0021] The ferrite powder may contain, in addition to Fe, at least one element selected from, for example, Mn, Zn, Mg, Sr, Ni, Cu, Ba, Co, Ca, Al, Li, Ti, Pb, Cd, etc. In one embodiment, the ferrite powder preferably contains, in addition to Fe, at least one element selected from Mn, Zn, Mg, Sr, and Ni.
[0022] Examples of the ferrite powder include Fe-Mn ferrite powder, Mg-Zn ferrite powder, Mn ferrite powder, Mn-Zn ferrite powder, Mn-Mg ferrite powder, Cu-Zn ferrite powder, Mg-Sr ferrite powder, Mn-Mg-Sr ferrite powder, Ni-Zn ferrite powder, Ni-Zn-Cu ferrite powder, Ba-Zn ferrite powder, Ba-Mg ferrite powder, Ba-Ni ferrite powder, Ba-Co ferrite powder, Ba-Ni-Co ferrite powder, Y ferrite powder, and the like.
[0023] The iron oxide powder is not particularly limited, but examples thereof include iron (III) oxide powder and triiron tetroxide powder.
[0024] The magnetic metal powder preferably contains at least one element selected from Fe, Co, and Ni. The content of Fe, Co, and Ni in the magnetic metal powder may be preferably 50 mass% or more, more preferably 60 mass% or more, and even more preferably 70 mass% or more. In addition to the element selected from Fe, Co, and Ni, the magnetic metal powder preferably contains an element selected from, for example, Si, Al, Cr, Mo, Cu, etc.
[0025] The magnetic metal powder is not particularly limited, but examples thereof include pure iron powder; crystalline or amorphous magnetic alloy powders such as Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Cr alloy powder, Fe-Si-Cr alloy powder, Fe-Ni-Cr alloy powder, Fe-Cr-Al alloy powder, Fe-Ni alloy powder, Fe-Ni-Mo alloy powder, Fe-Ni-Mo-Cu alloy powder, Fe-Co alloy powder, Fe-Ni-Co alloy powder, and Co-based amorphous alloy powder.
[0026] (A-1) The flat magnetic powder preferably contains a magnetic metal powder, more preferably contains a magnetic alloy powder, even more preferably contains a magnetic alloy powder selected from Fe-Si-Al alloy powder and Fe-Si-Cr alloy powder, and particularly preferably contains Fe-Si-Al alloy powder.
[0027] (A-1) 10% particle size of flat magnetic powder (D 10 ) is not particularly limited, but may be preferably 0.5 μm to 50 μm, more preferably 1 to 40 μm, further preferably 2 to 35 μm, and particularly preferably 3 to 30 μm.
[0028] (A-1) Average particle size of flat magnetic powder (D 50 From the viewpoint of suppressing magnetic loss as low as possible, the average particle diameter (D 50From the viewpoint of obtaining the effects of the invention more significantly, the lower limit of ) may be preferably 10 μm or more, more preferably 20 μm or more, further preferably 25 μm or more, and particularly preferably 30 μm or more.
[0029] (A-1) 90% particle size of flat magnetic powder (D 90 ) is not particularly limited, but may be preferably 30 μm to 200 μm, more preferably 40 to 150 μm, further preferably 50 to 140 μm, and particularly preferably 60 to 130 μm.
[0030] 10% particle size of magnetic powder (D 10 ), average particle size (D 50 ), and 90% particle size (D 90 ) can be measured and calculated by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution of the magnetic powder is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the 10% particle size (D 10 ), 50% particle size (average particle size) (D 50 ), and 90% particle size (D 90 ) can be calculated. A measurement sample can be preferably prepared by dispersing magnetic powder in pure water using ultrasonic waves. As a laser diffraction scattering type particle size distribution measuring device, the "MT3000II" manufactured by Microtrackbell, the "LA-960" manufactured by Horiba, Ltd., the "SALD-2200" manufactured by Shimadzu Corporation, etc. can be used.
[0031] The average thickness of the flat magnetic powder (A-1) is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.5 μm or more, from the viewpoint of further improving the magnetic permeability. The upper limit is preferably 40 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less, from the viewpoint of further improving the packing property. The average thickness of the magnetic powder is the average value of the thickness of the magnetic powder. For example, the average value of the thickness of the magnetic powder can be calculated by (Ym+Yn) / 2 based on the maximum value Ym and the minimum value Yn by measuring the thickness of, for example, 50 magnetic powder particles based on a scanning electron microscope image. The thickness of a magnetic powder refers to the length of the shortest side Y perpendicular to the longest side X of rectangular prism B when rectangular prism B with the smallest volume circumscribing the outer surface of magnetic powder particle A is drawn, with the longest side X being the same length as the longest axis of the line segment connecting any two points on the outer surface of magnetic powder particle A that are the longest distance apart (see Figure 16).
[0032] The average short axis length of the flat magnetic powder (A-1) is 1 μm or more from the viewpoint of keeping the viscosity low when the resin composition is made into a paste or a varnish for filming, and from the viewpoint of obtaining a desired magnetic permeability, and from the viewpoint of further improving the magnetic permeability, it is preferably 3 μm or more, more preferably 5 μm or more, even more preferably 8 μm or more, and particularly preferably 10 μm or more, and the upper limit is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less from the viewpoint of further improving the filling property. The average short axis length of the magnetic powder is the average value of the short axis length of the magnetic powder. The average value of the short axis length of the magnetic powder can be, for example, the number average when the short axis length of, for example, 50 magnetic powders is measured based on a scanning electron microscope image. The short axis length of a magnetic powder refers to the length of a third side Z perpendicular to both the longest side X and the shortest side Y perpendicular to the longest side X of a rectangular prism B when the longest axis is taken as the line segment connecting any two points on the outer surface of the magnetic powder particle A that are the longest distance apart, and when a rectangular prism B of the smallest volume that circumscribes the outer surface of the magnetic powder particle A is drawn, the longest side X of the rectangular prism B is parallel to the longest axis and has the same length as the longest axis (see Figure 16).
[0033] The flatness of the (A-1) flat magnetic powder is preferably 2 or more, more preferably 3 or more, even more preferably 5 or more, and particularly preferably 15 or more, from the viewpoint of further improving the magnetic permeability, and the upper limit is preferably 1000 or less, more preferably 650 or less, even more preferably 600 or less, and particularly preferably 550 or less, from the viewpoint of further improving the packing property. The flatness of the magnetic powder is a value calculated by dividing the "average major axis length of the magnetic powder (μm)" by the "average thickness of the magnetic powder (μm)". The average major axis length of the magnetic powder is the average value of the major axis length of the magnetic powder. The average value of the major axis length of the magnetic powder can be, for example, a number average when the major axis lengths of, for example, 50 magnetic powders are measured based on a scanning electron microscope image. The major axis length of the magnetic powder refers to the length of the line segment connecting two points that are the longest distance between any two points on the outer surface of the magnetic powder particle A (i.e., the length of the longest side X in the rectangular parallelepiped B shown in FIG. 16).
[0034] (A-1) The aspect ratio of the flat magnetic powder is preferably 1.0 or more, more preferably 1.2 or more, and even more preferably 1.5 or more, from the viewpoint of further improving the magnetic permeability, and the upper limit is preferably 6.0 or less, more preferably 5.0 or less, even more preferably 4.0 or less, even more preferably 3.5 or less, and particularly preferably 3.0 or less, from the viewpoint of further improving the filling property. The aspect ratio of the magnetic powder is a value calculated by dividing the "average major axis length of the magnetic powder (μm)" by the "average minor axis length of the magnetic powder (μm)".
[0035] The tap density of the (A-1) flat magnetic powder is preferably 0.5 to 4.0 g / cm from the viewpoint of further improving the packing property. 3 , more preferably 0.8 to 4.0 g / cm 3 , and more preferably 1.0 to 4.0 g / cm 3 , and even more preferably 1.5 to 4.0 g / cm 3 , particularly preferably 1.7 to 4.0 g / cm 3 The tap density can be a value obtained by measurement according to JIS Z2512.
[0036] The true specific gravity of the flat magnetic powder (A-1) is not particularly limited, but is, for example, 4 to 10 g / cm 3 It could be.
[0037] As the (A-1) flat magnetic powder, commercially available magnetic powders can be used. Specific examples of commercially available (A-1) flat magnetic powders include "PST-4" and "FME3D-AH" manufactured by Sanyo Special Steel Co., Ltd., and "JEMK S" and "JEMK H" manufactured by Kinsei Matec Co., Ltd. These may be used alone or in combination of two or more.
[0038] From the viewpoint of further improving the magnetic permeability, further improving the mixing of the (A-1) flat magnetic powder with the (A-2) spherical magnetic powder, and further reducing the viscosity, the content (volume %) of the flat magnetic powder (A-1) is preferably 1 vol% or more, more preferably 5 vol% or more, even more preferably 10 vol% or more, still more preferably 12 vol% or more, and particularly preferably 15 vol% or more, assuming that the nonvolatile components in the resin composition are 100 vol%, and the upper limit is preferably 70 vol% or less, more preferably 60 vol% or less, even more preferably 55 vol% or less, still more preferably 50 vol% or less, and particularly preferably 45 vol% or less.
[0039] From the viewpoints of further improving the magnetic permeability, further improving the mixing of the (A-1) flat magnetic powder with the (A-2) spherical magnetic powder, and further reducing the viscosity, the content (mass %) of the flat magnetic powder (A-1) is, relative to 100 mass % of the nonvolatile components in the resin composition, preferably 10 mass % or more, more preferably 20 mass % or more, even more preferably 25 mass % or more, and particularly preferably 30 mass % or more, and the upper limit is preferably 80 mass % or less, more preferably 70 mass % or less, even more preferably 65 mass % or less, and particularly preferably 60 mass % or less.
[0040] <(A-2) Spherical magnetic powder> In the resin composition of the present invention, the (A) magnetic powder includes (A-2) spherical magnetic powder. The (A-2) spherical magnetic powder may be used alone or in combination of two or more kinds.
[0041] The spherical magnetic powder (A-2) may be either a soft magnetic powder or a hard magnetic powder, but in one embodiment, from the viewpoint of obtaining the effect of the present invention remarkably, it is preferable that it is a soft magnetic powder. The spherical magnetic powder (A-2) may be, for example, a magnetic metal oxide powder, a magnetic metal powder, etc. Examples of the magnetic metal powder and the magnetic metal oxide powder are the same as those mentioned in the description of the flat magnetic powder (A-1), except that the external shape of the powder is different.
[0042] In one embodiment, the (A-2) spherical magnetic powder preferably contains a magnetic metal powder, more preferably contains a magnetic alloy powder, even more preferably contains a magnetic alloy powder selected from Fe-Si-Al alloy powder and Fe-Si-Cr alloy powder, and particularly preferably contains Fe-Si-Cr alloy powder.
[0043] The Fe-Si-Cr alloy powder contains Fe, Si and Cr. The amount of Fe in the Fe-Si-Cr alloy powder is preferably 75% by mass to 99% by mass, more preferably 80% by mass to 97% by mass, and particularly preferably 85% by mass to 95% by mass. The amount of Si in the Fe-Si-Cr alloy powder is preferably 2.0% by mass to 15.0% by mass, more preferably 3.5% by mass to 11.0% by mass, and particularly preferably 5.0% by mass to 9.5% by mass. The amount of Cr in the Fe-Si-Cr alloy powder is preferably 0.1% by mass to 10.0% by mass, more preferably 0.5% by mass to 8.0% by mass, and particularly preferably 1.0% by mass to 6.0% by mass. The Fe-Si-Cr alloy powder may also contain metal elements and semimetal elements other than Fe, Si, and Cr.
[0044] In one embodiment, the (A-2) spherical magnetic powder preferably contains a magnetic metal oxide powder, more preferably contains a ferrite powder, further preferably contains a ferrite powder selected from a Mn-based ferrite powder and a Mn-Zn-based ferrite powder, and particularly preferably contains a Mn-based ferrite powder.
[0045] The Mn-based ferrite powder contains Fe and Mn. When the total elements including O (oxygen) contained in the ferrite are taken as 100 mass%, the amount of Fe in the Mn-based ferrite powder is preferably 40 mass% or more, more preferably 45 mass% or more, particularly preferably 50 mass% or more, and also preferably 75 mass% or less, more preferably 70 mass% or less, and particularly preferably 65 mass% or less. When the total elements including O contained in the ferrite are taken as 100 mass%, the amount of Mn in the single crystal Mn-based ferrite powder is preferably 3 mass% or more, more preferably 5 mass% or more, particularly preferably 7 mass% or more, and also preferably 40 mass% or less, more preferably 35 mass% or less, and particularly preferably 30 mass% or less. The Mn-based ferrite powder may also contain elements such as metal elements and semimetal elements other than Fe and Mn. The amount of metal elements and metalloid elements other than Fe and Mn in the Mn-based ferrite powder is preferably less than 1 mass%, more preferably less than 0.7 mass%, and particularly preferably less than 0.5 mass%, when the total amount of all elements including O contained in the ferrite is taken as 100 mass%.
[0046] In one embodiment, the (A-2) spherical magnetic powder preferably includes a magnetic metal powder and a magnetic metal oxide powder, more preferably includes a magnetic alloy powder and a ferrite powder, even more preferably includes a magnetic alloy powder selected from an Fe-Si-Al alloy powder and an Fe-Si-Cr alloy powder, as well as a ferrite powder selected from an Mn ferrite powder and an Mn-Zn ferrite powder, and particularly preferably includes an Fe-Si-Cr alloy powder and an Mn ferrite powder.
[0047] (A-2) 10% particle size of spherical magnetic powder (D 10) is not particularly limited, but may be preferably 0.005 μm to 25 μm, more preferably 0.01 to 20 μm, and particularly preferably 0.03 to 15 μm.
[0048] (A-2) Average particle size of spherical magnetic powder (D 50 From the viewpoint of suppressing magnetic loss, the thickness is preferably 40 μm or less, more preferably 30 μm or less, even more preferably 20 μm or less, and particularly preferably 12 μm or less. The lower limit is not particularly limited, but may be preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.08 μm or more, and particularly preferably 0.1 μm or more.
[0049] (A-2) 90% particle size of spherical magnetic powder (D 90 ) is not particularly limited, but may be preferably 0.1 μm to 50 μm, more preferably 0.5 to 30 μm, further preferably 0.8 to 25 μm, and particularly preferably 1 to 20 μm.
[0050] The average thickness of the spherical magnetic powder (A-2) is, from the viewpoint of suppressing magnetic loss as low as possible, preferably 40 μm or less, more preferably 30 μm or less, even more preferably 20 μm or less, and particularly preferably 12 μm or less. The lower limit is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.08 μm or more, and particularly preferably 0.10 μm or more.
[0051] The flattening ratio of the spherical magnetic powder (A-2) is preferably less than 2, more preferably 1.5 or less, even more preferably 1.3 or less, and particularly preferably 1.2 or less. The lower limit can be 1, for example.
[0052] The aspect ratio of the spherical magnetic powder (A-2) is preferably 2 or less, more preferably 1.5 or less, even more preferably 1.3 or less, and particularly preferably 1.2 or less. The lower limit can be, for example, 1.
[0053] (A-2) The true specific gravity of the spherical magnetic powder is, for example, 4 to 10 g / cm 3 It could be.
[0054] The specific surface area of the spherical magnetic powder (A-2) is not particularly limited, but is preferably 0.05 m 2 / g or more, more preferably 0.1m 2 / g or more, more preferably 0.3m 2 / g or more. Also, preferably 30m 2 / g or less, more preferably 20m 2 / g or less, more preferably 15m 2 The specific surface area of the magnetic powder can be measured by the BET method.
[0055] As the (A-2) spherical magnetic powder, commercially available products can be used. Examples of commercially available spherical magnetic powder (A-2) include "M05S" and "M001" manufactured by Powdertech Co., Ltd.; "PST-S" manufactured by Sanyo Special Steel Co., Ltd.; "AW2-08", "AW2-08PF20F", "AW2-08PF10F", "AW2-08PF3F", "Fe-3.5Si-4.5CrPF20F", "Fe-50NiPF20F", and "Fe-80Ni-4MoPF20F" manufactured by Epson Atmix Corporation; "LD-M", "LD-MH", "KNI-106", "KNI-106GSM", "KNI-106GS", and "KN I-109, "KNI-109GSM", "KNI-109GS"; "KNS-415", "BSF-547", "BSF-029", "BSN-125", "BSN-125", "BSN-714", "BSN-828", "S-1281", "S-1641", "S-1651", "S-1470", "S-1511", "S-2430" manufactured by Toda Kogyo Co., Ltd.; "JR09P2" manufactured by Japan Metals and Chemical Industries Co., Ltd.; "Nanotek" manufactured by CIK Nanotech Co., Ltd.; "JEMK-S" and "JEMK-H" manufactured by Kinsei Matec Co., Ltd.; "Yttrium iron oxide" manufactured by ALDRICH Co., Ltd., etc. (A-2) Spherical magnetic powder may be used alone or in combination of two or more kinds.
[0056] From the viewpoint of further improving the mixing of the (A-1) flat magnetic powder and the (A-2) spherical magnetic powder and keeping the viscosity lower, the content (volume %) of the spherical magnetic powder (A-2) is preferably 1 vol% or more, more preferably 5 vol% or more, even more preferably 10 vol% or more, particularly preferably 15 vol% or more, 20 vol% or more, or 25 vol% or more, when the non-volatile components in the resin composition are taken as 100 vol%, and the upper limit is preferably 70 vol% or less, more preferably 60 vol% or less, even more preferably 55 vol% or less, and particularly preferably 50 vol% or less.
[0057] From the viewpoint of further improving the mixing of the (A-1) flat magnetic powder and the (A-2) spherical magnetic powder and keeping the viscosity lower, the content (mass %) of the spherical magnetic powder (A-2) is preferably 10 mass % or more, more preferably 20 mass % or more, even more preferably 30 mass % or more, even more preferably 40 mass % or more, and particularly preferably 50 mass % or more, with the upper limit being preferably 85 mass % or less, more preferably 80 mass % or less, even more preferably 75 mass % or less, even more preferably 70 mass % or less, and particularly preferably 65 mass % or less, when the non-volatile components in the resin composition are taken as 100 mass %.
[0058] The mass ratio of the flat magnetic powder (A-1) to the spherical magnetic powder (A-2) ((A-1) component / (A-2) component) may be, for example, 0.05 or more, 0.1 or more, and from the viewpoint of further improving the magnetic permeability, it is preferably 0.2 or more, more preferably 0.3 or more, even more preferably 0.4 or more, and particularly preferably 0.5 or more. The upper limit may be, for example, 50.0 or less, 10.0 or less, and from the viewpoint of further suppressing the viscosity, it is preferably 3.0 or less, more preferably 2.7 or less, even more preferably 2.5 or less, even more preferably 2.3 or less, and particularly preferably 2.2 or less.
[0059] The content (volume %) of the (A) magnetic powder is not particularly limited, but from the viewpoint of further improving the magnetic permeability, when the nonvolatile components in the resin composition are taken as 100 volume %, it is preferably 20 volume % or more, more preferably 25 volume % or more, even more preferably 30 volume % or more, even more preferably 40 volume % or more, and particularly preferably 45 volume % or more. In addition, the upper limit is not particularly limited, but when the nonvolatile components in the resin composition are taken as 100 volume %, it is preferably 85 volume % or less, more preferably 82 volume % or less, even more preferably 79 volume % or less, and particularly preferably 75 volume % or less.
[0060] The content (mass%) of the (A) magnetic powder is not particularly limited, but from the viewpoint of further improving the magnetic permeability, when the non-volatile components in the resin composition are taken as 100 mass%, it is preferably 50 mass% or more, more preferably 60 mass% or more, 70 mass% or more, even more preferably 75 mass% or more, 80 mass% or more, particularly preferably 85 mass% or more, 88 mass% or more. In addition, the upper limit is not particularly limited, but when the non-volatile components in the resin composition are taken as 100 mass%, it is preferably 97 mass% or less, more preferably 96 mass% or less, particularly preferably 95 mass% or less.
[0061] <(B) Thermosetting resin> The resin composition of the present invention contains (B) a thermosetting resin. Examples of (B) thermosetting resins include epoxy resins, epoxy acrylate resins, urethane acrylate resins, urethane resins, cyanate resins, polyimide resins, benzoxazine resins, unsaturated polyester resins, phenolic resins, melamine resins, and silicone resins, as well as curing agents (e.g., epoxy curing agents) that react with these resins.
[0062] The content (mass%) of (B) thermosetting resin is not particularly limited, but from the viewpoint of obtaining the effects of the invention more significantly, when the non-volatile components in the resin composition are taken as 100 mass%, it is preferably 0.1 mass% or more, more preferably 1 mass% or more, even more preferably 3 mass% or more, and particularly preferably 4 mass% or more. Also, from the viewpoint of obtaining the effects of the invention more significantly, when the non-volatile components in the resin composition are taken as 100 mass%, the upper limit is preferably 50 mass% or less, more preferably 30 mass% or less, even more preferably 20 mass% or less, and particularly preferably 17 mass% or less.
[0063] <(B-1) Epoxy resin> The resin composition of the present invention preferably contains an epoxy resin (B-1) as the thermosetting resin (B). The epoxy resin (B-1) refers to a resin having an epoxy group.
[0064] (B-1) Epoxy resins include, for example, bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, and the like. Resins, cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, phenolphthalimidine type epoxy resins, phenolphthalein type epoxy resins, etc. The (B-1) epoxy resins may be used alone or in combination of two or more.
[0065] The resin composition preferably contains, as the epoxy resin (B-1), an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the non-volatile components of the epoxy resin (B-1) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0066] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition of the present invention may contain only a liquid epoxy resin as the epoxy resin, or may contain only a solid epoxy resin, or may contain a combination of a liquid epoxy resin and a solid epoxy resin. The resin composition of the present invention preferably contains a liquid epoxy resin as the epoxy resin.
[0067] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0068] As the liquid epoxy resin, glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane dimethanol type epoxy resin, cyclic aliphatic glycidyl ether, and epoxy resin having a butadiene structure are preferred, and glycirol type epoxy resin, cyclic aliphatic glycidyl ether, bisphenol A type epoxy resin, and bisphenol F type epoxy resin are more preferred.
[0069] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX Corporation, "YX7400" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" ( bisphenol F type epoxy resin; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical; "630", "630LSD", "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA; "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA; "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX; "EX-991L" (alkyleneoxy and butadiene type epoxy resin) manufactured by Nagase ChemteX; "Celloxide 2021P" (alicyclic epoxy resin with ester structure) manufactured by Daicel ); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins having a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EG-280" (fluorene structure-containing epoxy resin) manufactured by Osaka Gas Chemicals Co., Ltd.; and "EX-201" (cyclic aliphatic glycidyl ether) manufactured by Nagase ChemteX Corporation.
[0070] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.
[0071] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, phenolphthalimidine type epoxy resins, and phenolphthalein type epoxy resins.
[0072] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; and "EXA-7311" manufactured by DIC Corporation. , "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN475V", "ESN4 100V" (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "Y Examples of epoxy resins include "X7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.These may be used alone or in combination of two or more.
[0073] The epoxy equivalent of the (B-1) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., even more preferably 70 g / eq. to 1,000 g / eq., and even more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0074] The weight average molecular weight (Mw) of the epoxy resin (B-1) is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0075] The content (mass%) of the (B-1) epoxy resin is not particularly limited, but from the viewpoint of obtaining the effects of the invention more significantly, when the non-volatile components in the resin composition are taken as 100 mass%, it is preferably 0.1 mass% or more, more preferably 1 mass% or more, even more preferably 2 mass% or more, and particularly preferably 3 mass% or more. Also, from the viewpoint of obtaining the effects of the invention more significantly, when the non-volatile components in the resin composition are taken as 100 mass%, the upper limit is preferably 50 mass% or less, more preferably 30 mass% or less, even more preferably 20 mass% or less, and particularly preferably 15 mass% or less.
[0076] <(B-2) Epoxy hardener> When the resin composition of the present invention contains an epoxy resin (B-1) as the thermosetting resin (B), it may contain an epoxy curing agent (B-2) as an optional component. The epoxy curing agent (B-2) has a function of reacting with the epoxy resin (B-1) to cure the resin composition.
[0077] The (B-2) epoxy curing agent is not particularly limited, but examples thereof include active ester curing agents, phenolic curing agents, carbodiimide curing agents, acid anhydride curing agents, amine curing agents, benzoxazine curing agents, cyanate ester curing agents, and thiol curing agents, etc. The (B-2) epoxy curing agent preferably contains an epoxy curing agent selected from phenolic curing agents and active ester curing agents, and particularly preferably contains a phenolic curing agent.
[0078] As the active ester curing agent, generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester compound is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester compound obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester compound obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0079] As the active ester curing agent, specifically, a dicyclopentadiene type active ester compound, a naphthalene type active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of phenol novolac, and an active ester compound containing a benzoylated product of phenol novolac are preferred, among which at least one selected from a dicyclopentadiene type active ester compound and a naphthalene type active ester compound is more preferred, and a dicyclopentadiene type active ester compound is even more preferred. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferred.
[0080] Commercially available active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "EXB-8000L", "EXB-8000L-65M", "EXB-8000L-65TM", "HPC-8000L-65TM", "HPC-8000", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); and active ester compounds containing a naphthalene structure, such as "HP-B-8151-62T", "EXB-8100L-65T", "EXB-8150-60T", and "EXB-8150- 62T", "EXB-9416-70BK", "HPC-8150-60T", "HPC-8150-62T", and "EXB-8" (manufactured by DIC Corporation); an active ester compound containing phosphorus, such as "EXB9401" (manufactured by DIC Corporation), an active ester compound which is an acetylated product of phenol novolac, such as "DC808" (manufactured by Mitsubishi Chemical Corporation), an active ester compound which is a benzoylated product of phenol novolac, such as "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester compound containing a styryl group and a naphthalene structure, such as "PC1300-02-65MA" (manufactured by Air Water Inc.).
[0081] As the phenol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure is preferable. Also, from the viewpoint of adhesion to the adherend, a nitrogen-containing phenol-based curing agent is preferable, and a triazine skeleton-containing phenol-based curing agent is more preferable. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, a triazine skeleton-containing phenol novolac resin is preferable. Specific examples of phenol-based curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "TD-2090-60M" manufactured by DIC Corporation.
[0082] Examples of the carbodiimide-based curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, such as aliphatic biscarbodiimides, such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides, such as phenylene-bis(xylylcarbodiimide); and aliphatic polycarbodiimides, such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide). ; polycarbodiimides such as aromatic polycarbodiimides such as poly(phenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide].
[0083] Commercially available carbodiimide curing agents include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie.
[0084] Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule, and a curing agent having two or more acid anhydride groups in one molecule is preferable. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and the like. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd., and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Clay Valley.
[0085] The amine-based curing agent may be a curing agent having one or more, preferably two or more, amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or secondary amine, and more preferably a primary amine. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. As the amine-based curing agent, commercially available products may be used, and examples thereof include "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.
[0086] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation; "HFB2006M" manufactured by Showa Polymer Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0087] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.
[0088] Examples of thiol-based curing agents include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0089] The reactive group equivalent of the epoxy curing agent (B-2) is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the epoxy curing agent (B-2) per equivalent of reactive group.
[0090] The content (mass%) of the (B-2) epoxy curing agent is not particularly limited, but is preferably 50 mass% or less, more preferably 30 mass% or less, further preferably 20 mass% or less, and particularly preferably 10 mass% or less, when the non-volatile components in the resin composition are 100 mass%. The lower limit may be, for example, 0 mass% or more, 0.05 mass% or more, 0.1 mass% or more, etc.
[0091] <(C) Curing accelerator> When the resin composition of the present invention contains an epoxy resin (B-1) as the thermosetting resin (B), it may contain a curing accelerator (C) as an optional component. The curing accelerator (C) has the function of accelerating the curing of the epoxy resin (B-1).
[0092] Examples of the (C) curing accelerator include imidazole-based curing accelerators, phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. In one embodiment, the (C) curing accelerator preferably includes a curing accelerator selected from an imidazole-based curing accelerator and a phosphorus-based curing accelerator. The (C) curing accelerator may be used alone or in combination of two or more.
[0093] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct imidazole compounds such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins.
[0094] As the imidazole-based curing accelerator, commercially available products may be used, for example, "1B2PZ", "2MZA-PW", and "2PHZ-PW" manufactured by Shikoku Chemical Industry Co., Ltd., and "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0095] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hydrogenhexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate ... aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.
[0096] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].
[0097] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.
[0098] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0099] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene.
[0100] As the amine-based curing accelerator, a commercially available product may be used, for example, "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0101] The content (mass%) of the (C) curing accelerator is not particularly limited, but is preferably 10 mass% or less, more preferably 5 mass% or less, further preferably 3 mass% or less, and particularly preferably 2 mass% or less, based on 100 mass% of the non-volatile components in the resin composition. The lower limit may be, for example, 0 mass% or more, 0.001 mass% or more, 0.01 mass% or more, etc.
[0102] <(D) Thermoplastic resin> The resin composition of the present invention may contain a thermoplastic resin (D) as an optional component. The thermoplastic resin (D) described here is a component that does not fall under the category of the thermosetting resin (B) described above.
[0103] (D) Examples of the thermoplastic resin include phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyimide resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. Among them, phenoxy resin is preferable. Moreover, the thermoplastic resin may be used alone or in combination of two or more kinds.
[0104] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.
[0105] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.
[0106] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0107] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.
[0108] Specific examples of polyimide resins include "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.
[0109] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0110] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0111] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0112] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.
[0113] From the viewpoint of obtaining the effects of the present invention remarkably, the weight average molecular weight (Mw) of the (D) thermoplastic resin is preferably 8,000 or more, more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 70,000 or less, more preferably 60,000 or less, particularly preferably 50,000 or less.
[0114] The content (mass%) of the (D) thermoplastic resin is not particularly limited, but is preferably 50 mass% or less, more preferably 20 mass% or less, even more preferably 10 mass% or less, and particularly preferably 6 mass% or less, when the non-volatile components in the resin composition are 100 mass%. The lower limit may be, for example, 0 mass% or more, 0.01 mass% or more, 0.1 mass% or more, 1 mass% or more, etc.
[0115] <(E) Dispersant> The resin composition of the present invention may contain a dispersant (E) as an optional component.
[0116] Examples of the (E) dispersant include phosphate ester dispersants such as polyoxyethylene alkyl ether phosphate; polyoxyalkylene dispersants such as polyoxyethylene alkyl ether, polyoxyethylene alkyl ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene alkylphenyl ether, polyoxyethylene alkylamine, and polyoxyethylene alkylamide; acetylene dispersants such as acetylene glycol; silicone dispersants such as polyether-modified polydimethylsiloxane, polyether-modified siloxane, and polyester-modified polydimethylsiloxane; anionic dispersants such as sodium polyacrylate, sodium dodecyl benzyl sulfonate, sodium laurate, ammonium polyoxyethylene alkyl ether sulfate, and sodium carboxymethyl cellulose; and cationic dispersants such as amino group-containing polyacrylate resins and amino group-containing polystyrene resins. The (E) dispersants may be used alone or in combination of two or more.
[0117] Commercially available phosphate ester dispersants include "RS-410," "RS-610," and "RS-710" from the "Phosphanol" series manufactured by Toho Chemical Industry Co., Ltd.
[0118] Commercially available polyoxyalkylene dispersants include "AKM-0531", "AFB-1521", "SC-0505K", "SC-1015F", "SC-0708A", and "HKM-50A" from the "Marialim" series manufactured by NOF Corporation.
[0119] Commercially available acetylene-based dispersants include the "Surfynol" series manufactured by Air Products and Chemicals Inc., including "82," "104," "440," "465," and "485," as well as "Olefin Y."
[0120] Commercially available silicone dispersants include "BYK347" and "BYK348" manufactured by BYK-Chemie.
[0121] Commercially available anionic dispersants include "PN-411" and "PA-111" manufactured by Ajinomoto Fine-Techno Co., Ltd.; "A-550" and "PS-1900" manufactured by Lion Corporation.
[0122] Commercially available cationic dispersants include "161", "162", "164", "182", "2000", and "2001" manufactured by BYK-Chemie; "PB-821", "PB-822", and "PB-824" manufactured by Ajinomoto Fine-Techno Co., Ltd.; "V-216" and "V-220" manufactured by ISP Japan; and "Solsperse 13940", "Solsperse 24000", and "Solsperse 32000" manufactured by Lubrizol Corporation.
[0123] The content (mass%) of the (E) dispersant is not particularly limited, but is preferably 20 mass% or less, more preferably 15 mass% or less, further preferably 10 mass% or less, and particularly preferably 7 mass% or less, based on 100 mass% of the non-volatile components in the resin composition. The lower limit may be, for example, 0 mass% or more, 0.01 mass% or more, 0.1 mass% or more, 1 mass% or more, etc.
[0124] <(F) Other additives> The resin composition of the present invention may further contain any additive as a non-volatile component. Examples of such additives include radical polymerizable compounds such as maleimide radical polymerizable compounds, vinylphenyl radical polymerizable compounds, (meth)acrylic radical polymerizable compounds, allyl radical polymerizable compounds, and polybutadiene radical polymerizable compounds; radical polymerization initiators such as peroxide radical polymerization initiators and azo radical polymerization initiators; organic fillers such as rubber particles; organometallic compounds such as organocopper compounds and organozinc compounds; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone leveling agents and acrylic polymer leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone defoamers, acrylic defoamers, fluorine defoamers, and vinyl resin defoamers. ; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silane; adhesion imparting agents such as triazole-based adhesion imparting agents, tetrazole-based adhesion imparting agents, and triazine-based adhesion imparting agents; antioxidants such as hindered phenol-based antioxidants; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers. (F) Other additives may be used alone or in combination of two or more at any ratio. The content of (F) other additives can be appropriately determined by those skilled in the art.
[0125] <(G) Organic solvent> The resin composition of the present invention may further contain an arbitrary organic solvent as a volatile component in addition to the non-volatile components described above. For example, when preparing a film from the resin composition, the resin composition may be made into a varnish with an organic solvent, and the varnish of the resin composition may be applied onto a support and dried to form a resin composition layer. In this case, the resin composition layer may contain a solvent as a residual solvent. As the (G) organic solvent, any known organic solvent may be used as long as it can dissolve at least a part of the non-volatile components, and the type of the organic solvent is not particularly limited. (G) Examples of organic solvents include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, and diphenyl ether; alcohol-based solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, and methyl methoxypropionate. ether alcohol-based solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, diethylene glycol monobutyl ether (butyl carbitol), and the like; amide-based solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and the like; sulfoxide-based solvents such as dimethyl sulfoxide, and the like; nitrile-based solvents such as acetonitrile, propionitrile, and the like; aliphatic hydrocarbon-based solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane, and the like; and aromatic hydrocarbon-based solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene, and the like.(G) organic solvent may be used alone or in any combination of two or more kinds in any ratio. (G) organic solvent, when used, may be used alone or in any combination of two or more kinds in any ratio.
[0126] The content of the (G) organic solvent is preferably as low as possible when the resin composition is made into a paste-like resin composition for printing or filling holes, and is preferably 1% by mass or less, more preferably 0.8% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less, when the total components in the resin composition are 100% by mass. There is no particular limit to the lower limit, and it can be, for example, 0.001% by mass, but it is ideally 0% by mass. When the resin composition is a varnish for film production, the content of the organic solvent is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 8% by mass or less, and particularly preferably 6% by mass or less, when the total components in the resin composition are 100% by mass. There is no particular limit to the lower limit, and it can be, for example, 0.001% by mass or more. The residual solvent in the film is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, and particularly preferably 1% by mass or less. There is no particular limit to the lower limit, and it can be, for example, 0.001% by mass or more. (G) By reducing the content of the organic solvent, it is possible to prevent the generation of voids due to the evaporation of the organic solvent, and further to provide excellent handling and workability.
[0127] <Characteristics of resin composition> The resin composition of the present invention includes (A) a magnetic powder and (B) a thermosetting resin, the magnetic powder (A) includes (A-1) a flat magnetic powder and (A-2) a spherical magnetic powder, and the average minor axis length of the flat magnetic powder (A-1) is 1 μm or more. By using such a resin composition, a magnetic material that is easy to form into a paste or a film and has excellent relative magnetic permeability can be obtained.
[0128] The cured product of the resin composition of the present invention can have an excellent relative magnetic permeability (μ'). Thus, in one embodiment, the relative magnetic permeability (μ') of the cured product of the resin composition, as measured at a measurement frequency of 10 MHz and 23°C as in the following Test Example 2, can be preferably 4 or more, 6 or more, more preferably 8 or more, 10 or more, 11 or more, even more preferably 12 or more, 13 or more, and particularly preferably 14 or more, 15 or more.
[0129] In one embodiment, the resin composition of the present invention may have a suitable viscosity. Therefore, in one embodiment, when the resin composition is used as a paste for filling holes, the viscosity at 25°C (±2°C) measured using an E-type viscometer as in the following Test Example 3 is preferably 0.05 Pa·s or more, more preferably 0.1 Pa·s or more, even more preferably 0.5 Pa·s or more, and particularly preferably 1 Pa·s or more, and the upper limit is preferably 1500 Pa·s or less, more preferably 1200 Pa·s or less, even more preferably 1000 Pa·s or less, and particularly preferably 800 Pa·s or less.
[0130] When used as a paste (varnish) for producing a film, the viscosity at 25°C (±2°C) measured using an E-type viscometer as in Test Example 3 below is preferably 0.05 Pa·s or more, more preferably 0.1 Pa·s or more, even more preferably 0.5 Pa·s or more, and particularly preferably 1 Pa·s or more, and the upper limit is preferably 200 Pa·s or less, more preferably 100 Pa·s or less, even more preferably 80 Pa·s or less, and particularly preferably 50 Pa·s or less.
[0131] <Method of producing resin composition> The resin composition of the present invention can be produced, for example, by adding (A) magnetic powder, (B) thermosetting resin, if necessary (C) curing accelerator, if necessary (D) thermoplastic resin, if necessary (E) dispersant, if necessary (F) other additives, and if necessary (G) organic solvent to an arbitrary preparation vessel in any order and / or all at once and mixing. In addition, the temperature can be appropriately set in the process of adding and mixing each component, and heating and / or cooling may be performed temporarily or throughout. In addition, stirring or shaking may be performed in the process of adding and mixing each component. In addition, during or after adding and mixing, the resin composition may be stirred or shaken using a stirring device or shaking device such as a mixer to disperse uniformly. In addition, degassing may be performed under low pressure conditions such as under vacuum at the same time as stirring or shaking.
[0132] <Form of Resin Composition> In forming the magnetic cured material of the substrate, the resin composition may be used in the form of a paste-like resin composition at room temperature (25°C (±2°C)), or in the form of a resin sheet including a layer of the resin composition. The paste-like resin composition may be, for example, a resin composition having a viscosity of 0.05 Pa s to 1500 Pa s at room temperature (25°C (±2°C)) as measured using an E-type viscometer as in Test Example 3 below.
[0133] In one embodiment, the resin composition may be a paste-like resin composition using an organic solvent, or a liquid thermosetting resin such as a liquid epoxy resin may be used to form a paste-like resin composition that does not contain an organic solvent.
[0134] In one embodiment, the resin composition can be suitably used as a resin composition for filling through holes. Also, in one embodiment, the resin composition can be suitably used as a resin composition for forming an inductor base element for producing an inductor element.
[0135] <Resin sheet> The resin sheet includes a support and a resin composition layer formed from the resin composition of the present invention provided on the support.
[0136] From the viewpoint of thinning, the thickness of the resin composition layer is preferably 250 μm or less, more preferably 200 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 5 μm or more, 10 μm or more, etc.
[0137] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0138] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylic polymers such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0139] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0140] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment or a corona treatment.
[0141] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd-based release agents, polyolefin-based release agents, urethane-based release agents, and silicone-based release agents. The support with a release layer may be a commercially available product, for example, "PET501010", "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of a silicone-based release agent or an alkyd resin-based release agent.
[0142] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.
[0143] In the resin sheet, a protective film equivalent to the support can be further laminated on the surface of the resin composition layer not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and scratches on the surface of the resin composition layer. The resin sheet can be stored in a roll shape. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0144] The resin sheet can be produced, for example, by applying the resin composition onto a support using a die coater or the like to form a resin composition layer. If necessary, the resin composition may be mixed with an organic solvent and then applied onto the support. When an organic solvent is used, drying may be performed after application if necessary.
[0145] Drying may be performed by heating, blowing hot air, or the like. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the components contained in the resin composition, drying at 50°C to 150°C for 3 minutes to 10 minutes can form a resin composition layer.
[0146] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0147] <Circuit board and its manufacturing method> The circuit board of the present invention includes a cured product of a resin composition. The circuit board of the first embodiment includes a substrate having a through hole and a cured product of the resin composition of the present invention filled in the through hole. The circuit board of the second embodiment includes a cured product layer formed by a cured product of a resin composition layer of a resin sheet. Hereinafter, the first and second embodiments of the method for manufacturing a circuit board will be described. However, the method for manufacturing a circuit board according to the present invention is not limited to the first and second embodiments exemplified below.
[0148] First Embodiment The circuit board of the first embodiment is manufactured, for example, by a manufacturing method including the following steps (1) to (5). In the first embodiment, it is preferable to form a cured product using a resin composition, and it is more preferable to form a cured product using a paste-like resin composition. (1) filling a through-hole of a substrate having a through-hole with a resin composition; (2) a step of thermally curing the resin composition to obtain a cured product; (3) A step of polishing the surface of the cured product or the resin composition; (4) roughening the cured product; and (5) forming a conductive layer on the roughened surface of the cured product. The method for producing a circuit board of the present invention may be carried out in the order of steps (1) to (5), or step (2) may be carried out after step (3).
[0149] <Process (1)> The step (1) may include a step of preparing a resin composition. The resin composition is as described above.
[0150] 1, the process may include a step of preparing a core substrate 10 including a support substrate 11, a first metal layer 12 made of a metal such as copper foil provided on both surfaces of the support substrate 11, and a second metal layer 13. Examples of materials for the support substrate 11 include insulating substrates such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. Examples of materials for the first and second metal layers include copper foil with a carrier, and materials for the conductor layers described later.
[0151] 2, a step of forming through holes 14 in the core substrate 10 may be included. The through holes 14 can be formed by, for example, drilling, laser irradiation, plasma irradiation, etc. Specifically, the through holes 14 can be formed by forming through holes in the core substrate 10 using a drill or the like.
[0152] The through holes 14 can be formed by using a commercially available drilling device. An example of a commercially available drilling device is "ND-1S211" manufactured by Hitachi Via Mechanics.
[0153] After forming through holes 14 in core substrate 10, the process may include a step of roughening core substrate 10 and forming plating layer 20 within through holes 14, on the surface of first metal layer 12, and on the surface of second metal layer 13, as shown in an example in FIG. 3.
[0154] The roughening treatment may be either a dry or wet roughening treatment. An example of the dry roughening treatment is a plasma treatment. An example of the wet roughening treatment is a method in which a swelling treatment using a swelling liquid, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing liquid are performed in this order.
[0155] The plating layer 20 is formed by a plating method, and the procedure for forming the plating layer 20 by a plating method is similar to the formation of the conductive layer in step (5) described below.
[0156] After preparing the core substrate 10, the through-holes 14 are filled with the resin composition 30a, as shown in FIG. 4. The filling can be performed by, for example, a printing method. Examples of the printing method include a method of printing the resin composition 30a into the through-holes 14 using a squeegee, a method of printing the resin composition 30a using a cartridge, a method of printing the resin composition 30a by mask printing, a roll coating method, an inkjet method, and the like.
[0157] <Process (2)> In step (2), the through-hole 14 is filled with the resin composition 30a, and the resin composition 30a is thermally cured to form a cured product 30 in the through-hole 14, as shown in FIG. 5. The thermal curing conditions of the resin composition 30a vary depending on the composition and type of the resin composition 30a, but the curing temperature is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher, and is preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The curing time of the resin composition 30a is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and is preferably 120 minutes or lower, more preferably 110 minutes or lower, and even more preferably 100 minutes or lower.
[0158] The degree of cure of the cured product 30 in step (2) is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The degree of cure can be measured, for example, by using a differential scanning calorimeter.
[0159] Before the resin composition 30a is thermally cured, the resin composition 30a may be subjected to a preheating treatment in which the resin composition 30a is heated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition 30a, the resin composition 30a may be preheated at a temperature of usually 50° C. or higher and lower than 120° C. (preferably 60° C. or higher and 110° C. or lower, more preferably 70° C. or higher and 100° C. or lower) for usually 5 minutes or longer (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes).
[0160] <Process (3)> In step (3), as shown in Fig. 6, the excess cured material 30 protruding from or adhering to the core substrate 10 is removed by polishing to flatten the surface. As the polishing method, any method capable of polishing the excess cured material 30 protruding from or adhering to the core substrate 10 can be used. Examples of such polishing methods include buff polishing and belt polishing. An example of a commercially available buff polishing device is "NT-700IM" manufactured by Ishii Hyoki Co., Ltd.
[0161] The arithmetic mean roughness (Ra) of the polished surface of the cured material 30 (after the cured material layer is thermally cured) is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the plating. The upper limit is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0162] When step (3) is carried out after step (2), a heat treatment may be carried out after step (2) and before step (3) as necessary for the purpose of further increasing the degree of curing of the cured product 30. The temperature in the heat treatment may be in accordance with the above-mentioned curing temperature, and is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher, and is preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The heat treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and is preferably 90 minutes or lower, more preferably 70 minutes or lower, and even more preferably 60 minutes or lower.
[0163] In addition, when step (3) is performed before step (2), a preheating treatment may be performed before step (3) by heating at a temperature lower than the curing temperature of the resin composition. The temperature in the preheating treatment is preferably 100° C. or higher, more preferably 110° C. or higher, and even more preferably 120° C. or higher, and preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The heat treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and preferably 90 minutes or less, more preferably 70 minutes or less, and even more preferably 60 minutes or less.
[0164] <Process (4)> In step (4), the surface polished in step (3) is roughened (desmeared). The procedure and conditions of the roughening step are not particularly limited, and known procedures and conditions that are usually used in the manufacturing method of a multilayer printed wiring board can be adopted. As the roughening step, for example, the cured product 30 can be roughened by performing a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.
[0165] The swelling liquid that can be used in the roughening step is not particularly limited, but includes an alkaline solution, a surfactant solution, and the like, and is preferably an alkaline solution. As the alkaline solution that is the swelling liquid, a sodium hydroxide solution and a potassium hydroxide solution are more preferable. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan.
[0166] The swelling treatment with the swelling liquid is not particularly limited, but can be carried out, for example, by immersing the core substrate 20 provided with the cured material 30 for 1 to 20 minutes in a swelling liquid at 30° C. to 90° C. From the viewpoint of suppressing swelling of the resin constituting the cured material 30 to an appropriate level, it is preferable to immerse the cured material 30 in a swelling liquid at 40° C. to 80° C. for 5 to 15 minutes.
[0167] The oxidizing agent that can be used in the roughening treatment with an oxidizing agent is not particularly limited, and examples thereof include an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment with an oxidizing agent such as an alkaline permanganate solution is preferably carried out by immersing the cured material 30 in a solution of the oxidizing agent heated to 60°C to 80°C for 10 minutes to 30 minutes. In addition, the concentration of the permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact P" and "Dosing Solution Securigans P" manufactured by Atotech Japan.
[0168] The neutralizing liquid used in the neutralization treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigans P" manufactured by Atotech Japan. The neutralization treatment with a neutralizing liquid can be carried out by immersing the treated surface that has been roughened with an oxidizing solution in a neutralizing liquid at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the cured material 30 that has been roughened with an oxidizing solution is immersed in a neutralizing liquid at 40°C to 70°C for 5 to 20 minutes is preferred.
[0169] The arithmetic mean roughness (Ra) of the cured product 30 after roughening treatment is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the plating. The upper limit is preferably 1500 nm or less, more preferably 1200 nm or less, and even more preferably 1000 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0170] <Process (5)> In step (5), a conductor layer 40 is formed on the polished surface of the cured product 30 and on the core substrate, as shown in an example in Fig. 7. After the conductor layer 40 is formed, a patterned conductor layer 41 may be formed by removing parts of the conductor layer 40, the first metal layer 12, the second metal layer 13, and the plating layer 20 by a process such as etching, as shown in an example in Fig. 8. In Fig. 7, the conductor layer 40 is formed on both sides of the core substrate 10, but the conductor layer 40 may be formed on only one side of the core substrate 10.
[0171] The method for forming the conductor layer 40 includes, for example, plating, sputtering, vapor deposition, etc., among which plating is preferred. In a preferred embodiment, the surface of the cured material 30 (and the plating layer 20) is plated by an appropriate method such as a semi-additive method or a full-additive method to form a patterned conductor layer 41 having a desired wiring pattern. Examples of materials for the conductor layer 40 include single metals such as gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium; and alloys of two or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. Among these, from the viewpoints of versatility, cost, ease of patterning, and the like, it is preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy, it is more preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, and it is even more preferable to use copper.
[0172] Here, an example of an embodiment in which a patterned conductor layer 41 is formed on the polished surface of the cured product 30 will be described in detail. A plating seed layer is formed on the polished surface of the cured product 30 by electroless plating. Next, an electrolytic plating layer is formed on the formed plating seed layer by electrolytic plating, and unnecessary plating seed layer is removed by etching or other treatment as necessary to form a conductor layer 40 having a desired wiring pattern. After the formation of the conductor layer 40, an annealing treatment may be performed as necessary for the purpose of improving the peel strength of the conductor layer 40. The annealing treatment can be performed, for example, by heating the circuit board at 150 to 200°C for 20 to 90 minutes.
[0173] From the viewpoint of thinning, the thickness of the patterned conductor layer is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.
[0174] <Second embodiment> The circuit board of the second embodiment includes a cured layer formed by a cured product of the resin composition. In the second embodiment, it is preferable to form the cured layer using a resin sheet. Hereinafter, the second embodiment of the method for manufacturing the product substrate will be described. Explanations of parts that overlap with the first embodiment will be omitted as appropriate.
[0175] The circuit board of the second embodiment is manufactured, for example, by a manufacturing method including the following steps (A) to (D). (A) a step of laminating a resin sheet onto an inner layer substrate such that the resin composition layer is bonded to the inner layer substrate to form a cured material layer; (B) a step of drilling holes in the cured layer; (C) a step of roughening the surface of the cured layer; and (D) forming a conductive layer on the polished surface of the cured layer.
[0176] The above steps (A) to (D) for manufacturing the circuit board will now be described in detail.
[0177] <Process (A)> Step (A) is a step of laminating a resin sheet on an inner layer substrate such that the resin composition layer is bonded to the inner layer substrate to form a cured layer. In one embodiment of step (A), a resin sheet is laminated on an inner layer substrate such that the resin composition layer is bonded to the inner layer substrate, and the resin composition layer is thermally cured to form a cured layer.
[0178] In step (A), as shown in an example in Figure 9, a resin sheet 310 including a support 330 and a resin composition layer 320a provided on the support 330 is laminated onto an inner layer substrate 200 so that the resin composition layer 320a is bonded to the inner layer substrate 200.
[0179] The inner layer substrate 200 is an insulating substrate. Examples of materials for the inner layer substrate 200 include insulating base materials such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The inner layer substrate 200 may be an inner layer circuit substrate having wiring and the like built into its thickness.
[0180] As shown in Fig. 9 as an example, the inner layer substrate 200 has a first conductor layer 420 provided on the first main surface 200a and an external terminal 240 provided on the second main surface 200b. The first conductor layer 420 may include a plurality of wirings. In the illustrated example, only the wirings constituting the coil-shaped conductive structure 400 of the inductor element are shown. The external terminal 240 is a terminal for electrically connecting to an external device or the like (not shown). The external terminal 240 can be configured as a part of the conductor layer provided on the second main surface 200b.
[0181] The conductive material that can form the first conductive layer 420 and the external terminals 240 is similar to the material of the conductive layer explained in the section “<Step (5)>” of the first embodiment.
[0182] The first conductor layer 420 and the external terminal 240 may have a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different types of metals or alloys are laminated. The thickness of the first conductor layer 420 and the external terminal 240 is the same as that of the second conductor layer 440 described later.
[0183] The line (L) / space (S) ratio of the first conductor layer 420 and the external terminal 240 is not particularly limited, but from the viewpoint of reducing surface irregularities and obtaining a cured layer with excellent smoothness, it is usually 900 / 900 μm or less, preferably 700 / 700 μm or less, more preferably 500 / 500 μm or less, even more preferably 300 / 300 μm or less, and even more preferably 200 / 200 μm or less. The lower limit of the line / space ratio is not particularly limited, but from the viewpoint of improving embedding of the resin composition layer in the space, it is preferably 1 / 1 μm or more.
[0184] The inner layer substrate 200 may have a plurality of through holes 220 penetrating the inner layer substrate 200 from the first main surface 200a to the second main surface 200b. The through holes 220 are provided with through hole wiring 220a. The through hole wiring 220a electrically connects the first conductor layer 420 and the external terminal 240.
[0185] The resin composition layer 320a and the inner layer substrate 200 can be bonded, for example, by thermocompression bonding the resin sheet 310 to the inner layer substrate 200 from the support 330 side. Examples of a member for thermocompression bonding the resin sheet 310 to the inner layer substrate 200 (hereinafter also referred to as a "thermocompression bonding member") include a heated metal plate (such as a stainless steel (SUS) plate) or a metal roll (SUS roll). Note that, rather than pressing the resin sheet 310 by directly contacting it with the thermocompression bonding member, it is preferable to press the resin sheet 310 via a sheet made of an elastic material such as heat-resistant rubber so that the resin sheet 310 can sufficiently follow the irregularities on the surface of the inner layer substrate 200.
[0186] The temperature during thermocompression bonding is preferably in the range of 80°C to 160°C, more preferably 90°C to 140°C, and even more preferably 100°C to 120°C, the pressure during thermocompression bonding is preferably in the range of 0.098MPa to 1.77MPa, more preferably 0.29MPa to 1.47MPa, and the time during thermocompression bonding is preferably in the range of 20 seconds to 400 seconds, and more preferably 30 seconds to 300 seconds. The resin sheet and the inner layer substrate are preferably bonded under reduced pressure conditions of 26.7hPa or less.
[0187] The resin composition layer 320a of the resin sheet 310 can be bonded to the inner layer substrate 200 by a commercially available vacuum laminator. Examples of commercially available vacuum laminators include a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd. and a vacuum applicator manufactured by Nikko Materials Co., Ltd.
[0188] After bonding the resin sheet 310 and the inner layer substrate 200, the laminated resin sheet 310 may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support 330 side. The pressing conditions for the smoothing process may be the same as the thermocompression conditions for the lamination. The smoothing process may be performed using a commercially available laminator. Note that the lamination and the smoothing process may be performed successively using the commercially available vacuum laminator.
[0189] After the resin sheet 310 is laminated on the inner substrate 200, the resin composition layer 320a is thermally cured to form a cured layer. As shown in an example in FIG. 10, the resin composition layer 320a bonded to the inner substrate 200 is thermally cured to form a first cured layer 320.
[0190] The thermal curing conditions of the resin composition layer 320a vary depending on the composition and type of the resin composition, but the curing temperature is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher, and preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The curing time of the resin composition layer 320a is preferably 5 minutes or higher, more preferably 10 minutes or higher, and even more preferably 15 minutes or higher, and preferably 120 minutes or lower, more preferably 110 minutes or lower, and even more preferably 100 minutes or lower.
[0191] The support 330 may be removed between the end of the thermal curing in step (A) and step (B), or may be peeled off after step (B).
[0192] The arithmetic mean roughness (Ra) of the cured layer before roughening treatment is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the plating. The upper limit is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0193] In step (A), instead of using a resin sheet, a resin composition may be applied onto the inner layer substrate 200 using a die coater or the like, and then thermally cured to form a cured layer.
[0194] <Process (B)> In step (B), as shown in FIG. 11, the first cured material layer 320 is drilled to form a via hole 360. The via hole 360 serves as a path for electrically connecting the first conductor layer 420 and a second conductor layer 440 described below. The via hole 360 may be formed using, for example, a drill, a laser, plasma, or the like, depending on the composition of the resin composition used to form the cured material layer. The dimensions and shape of the hole may be appropriately determined depending on the design of the printed wiring board.
[0195] <Process (C)> In step (C), the surface of the cured layer in which the via holes are formed is roughened. The roughening treatment in step (C) is as described in the section “<Step (4)>” of the first embodiment.
[0196] The arithmetic mean roughness (Ra) of the cured layer after roughening treatment is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the plating. The upper limit is preferably 1500 nm or less, more preferably 1200 nm or less, and even more preferably 1000 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0197] <Process (D)> In the step (D), a second conductor layer 440 is formed on the first cured material layer 320, as shown in an example in FIG.
[0198] The conductive material that can form the second conductive layer 440 is similar to the material of the conductive layer explained in the section “<Step (5)>” of the first embodiment.
[0199] From the viewpoint of thinning, the thickness of the second conductor layer 440 is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.
[0200] The second conductor layer 440 can be formed by plating. The second conductor layer 440 is preferably formed by a wet plating method such as a semi-additive method or a full-additive method including an electroless plating process, a mask pattern forming process, an electrolytic plating process, and a flash etching process. By forming the second conductor layer 440 using a wet plating method, it is possible to form the second conductor layer 440 including a desired wiring pattern. Note that this process also forms an in-via-hole wiring 360a in the via hole 360.
[0201] The first conductor layer 420 and the second conductor layer 440 may be provided in a spiral shape, for example, as shown in Figs. 13 to 15 described later. In one example, one end of the spiral wiring part of the second conductor layer 440 on the center side is electrically connected to one end of the spiral wiring part of the first conductor layer 420 on the center side by the via-hole wiring 360a. The other end of the spiral wiring part of the second conductor layer 440 on the outer periphery side is electrically connected to the land 420a of the first conductor layer 42 by the via-hole wiring 360a. Therefore, the other end of the spiral wiring part of the second conductor layer 440 on the outer periphery side is electrically connected to the external terminal 240 via the via-hole wiring 360a, the land 420a, and the through-hole wiring 220a.
[0202] The coil-shaped conductive structure 400 is composed of a spiral wiring portion that is a part of the first conductor layer 420, a spiral wiring portion that is a part of the second conductor layer 440, and via-hole wiring 360a that electrically connects the spiral wiring portion of the first conductor layer 420 and the spiral wiring portion of the second conductor layer 440.
[0203] After step (D), a step of forming a hardened material layer on the conductor layer may be performed. In detail, as shown in an example in Fig. 14, a second hardened material layer 340 is formed on the first hardened material layer 320 on which the second conductor layer 440 and the via-hole wiring 360a are formed. The second hardened material layer may be formed by the same steps as those already described.
[0204] <Inductor board> The inductor substrate includes the circuit substrate of the present invention. When such an inductor substrate includes a circuit substrate obtained by the method for producing a circuit substrate according to the first embodiment, the inductor substrate has an inductor pattern formed by a conductor at least in a part of the periphery of the cured product of the resin composition. For example, the inductor substrate described in JP 2016-197624 A can be used.
[0205] Furthermore, when the inductor substrate includes a circuit board obtained by the method for producing a circuit board according to the second embodiment, the inductor substrate has a hardened layer and a conductive structure at least partially embedded in the hardened layer, and includes an inductor element formed by the conductive structure and a part of the hardened layer that extends in the thickness direction of the hardened layer and is surrounded by the conductive structure. Here, Fig. 13 is a schematic plan view of the inductor substrate having an inductor element as viewed from one side in the thickness direction. Fig. 14 is a schematic view showing a cut end surface of the inductor substrate cut at the position indicated by the dashed line II-II in Fig. 13. Fig. 15 is a schematic plan view for explaining the configuration of a first conductor layer in the inductor substrate.
[0206] 13 and 14, the circuit board 100 is a build-up wiring board having a plurality of cured material layers (first cured material layer 320, second cured material layer 340) and a plurality of conductor layers (first conductor layer 420, second conductor layer 440), i.e., a build-up cured material layer and a build-up conductor layer. The inductor board 100 also includes an inner layer board 200.
[0207] 14, the first cured material layer 320 and the second cured material layer 340 constitute the magnetic part 300, which can be seen as an integrated cured material layer. Therefore, the coil-shaped conductive structure 400 is provided so that at least a portion thereof is embedded in the magnetic part 300. That is, in the inductor substrate 100 of this embodiment, the inductor element is constituted by the coil-shaped conductive structure 400 and a core portion which is a portion of the magnetic part 300 that extends in the thickness direction of the magnetic part 300 and is surrounded by the coil-shaped conductive structure 400.
[0208] 15, the first conductor layer 420 includes a spiral wiring portion for constituting the coil-shaped conductive structure 400, and a rectangular land 420a electrically connected to the through-hole wiring 220a. In the illustrated example, the spiral wiring portion includes a straight portion and a bent portion that is bent at a right angle, and a detour portion that detours around the land 420a. In the illustrated example, the spiral wiring portion of the first conductor layer 420 has an overall outline that is approximately rectangular, and has a shape that winds counterclockwise from the center toward the outside.
[0209] Similarly, a second conductor layer 440 is provided on the first cured material layer 320. The second conductor layer 440 includes a spiral wiring portion for forming a coil-shaped conductive structure 400. In Fig. 13 or 14, the spiral wiring portion includes a straight portion and a bent portion bent at a right angle. In Fig. 13 or 14, the spiral wiring portion of the second conductor layer 44 has an overall outline that is substantially rectangular, and has a shape that is wound clockwise from the center toward the outside.
[0210] Such an inductor substrate can be used as a wiring board for mounting electronic components such as semiconductor chips, and can also be used as a (multilayer) printed wiring board using such a wiring board as an inner layer substrate.Furthermore, such a wiring board can be used as an individual chip inductor component, and can also be used as a printed wiring board with the chip inductor component surface mounted.
[0211] In addition, various types of semiconductor devices can be manufactured using such a wiring board. The semiconductor device including such a wiring board can be suitably used in electric products (e.g., computers, mobile phones, digital cameras, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES
[0212] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "%" representing an amount means "% by mass" unless otherwise specified. Unless otherwise specified, the temperature condition is room temperature (23°C). Unless otherwise specified, the pressure condition is normal pressure (1 atm).
[0213] <Example 1> Flat magnetic powder a (Sanyo Special Steel Co., Ltd. "PST-4", Fe-Si-Al alloy powder, 10% particle size (D 10 )5.8μm, average particle size (D 50 )37μm, 90% particle size (D 90 ) 75μm, aspect ratio 2.0, average thickness 1.7μm, flatness 22, average minor axis length 21μm, tap density 2.56g / cm 3 ) 50 parts by mass, spherical magnetic powder a (Epson Atmix "AW2-08PF3", Fe-Si-Cr alloy powder, 10% particle size (D 10 )1.7μm, average particle size (D 50 )3.1μm, 90% particle size (D 90 ) 5.2 μm, aspect ratio 1.1, average thickness 3.1 μm, flatness 1.1) 39 parts by mass, spherical magnetic powder b (M001 manufactured by Powder Tech Co., Ltd., Mn ferrite powder, 10% particle size (D 10 )0.05μm, average particle size (D 50 )0.12μm, 90% particle size (D 90 ) 1.1μm, aspect ratio 1.1, average thickness 0.1μm, aspect ratio 1.1), 39 parts by mass of epoxy resin (Nippon Steel Sumikin Chemical Co., Ltd. "ZX-1059", a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin), 13 parts by mass of phenol resin (DIC Corporation "LA-7054", melamine modified phenol novolac resin, MEK solution with 60% non-volatile components), 14 parts by mass of phenoxy resin (Mitsubishi Chemical Corporation "YX7553BH30", a 1:1 solution of methyl ethyl ketone:cyclohexanone with 30% non-volatile components, special skeleton phenoxy resin), and 0.1 parts by mass of curing accelerator a (Hokuko Chemical Industry Co., Ltd. "TBP-DA", a phosphorus-based curing accelerator) were added and uniformly dispersed using a high-speed rotating mixer to prepare a resin composition.
[0214] <Example 2> A resin composition was prepared in the same manner as in Example 1, except that the amount of flat magnetic powder a ("PST-4" manufactured by Sanyo Special Steel Co., Ltd.) used was changed from 50 parts by mass to 79 parts by mass, the amount of spherical magnetic powder a ("AW2-08PF3" manufactured by Epson Atmix) used was changed from 39 parts by mass to 61 parts by mass, and the amount of spherical magnetic powder b ("M001" manufactured by Powder Tech Co., Ltd.) used was changed from 39 parts by mass to 79 parts by mass.
[0215] <Example 3> A resin composition was prepared in the same manner as in Example 1, except that the amount of flat magnetic powder a ("PST-4" manufactured by Sanyo Special Steel Co., Ltd.) used was changed from 50 parts by mass to 87 parts by mass, the amount of spherical magnetic powder a ("AW2-08PF3" manufactured by Epson Atmix) used was changed from 39 parts by mass to 67 parts by mass, and the amount of spherical magnetic powder b ("M001" manufactured by Powder Tech Co., Ltd.) used was changed from 39 parts by mass to 87 parts by mass.
[0216] <Example 4> Instead of 50 parts by mass of flat magnetic powder a (Sanyo Special Steel Co., Ltd.'s "PST-4"), flat magnetic powder b (Sanyo Special Steel Co., Ltd.'s "FME3D-AH", Fe-Si-Al alloy powder, 10% particle size (D 10 )15μm, average particle size (D 50 )42μm, 90% particle size (D 90 ) 107μm, aspect ratio 2.0, thickness 0.1μm, flatness 480, average minor axis length 18μm, tap density 0.73g / cm 3 A resin composition was prepared in the same manner as in Example 1, except that 70 parts by mass of spherical magnetic powder a ("AW2-08PF3" manufactured by Epson Atmix) was used, the amount of spherical magnetic powder a ("AW2-08PF3" manufactured by Epson Atmix) was changed from 39 parts by mass to 58 parts by mass, and the amount of spherical magnetic powder b ("M001" manufactured by Powder Tech Co., Ltd.) was changed from 39 parts by mass to 73 parts by mass.
[0217] <Example 5> The amount of flat magnetic powder a (Sanyo Special Steel Co., Ltd. "PST-4") used was changed from 50 parts by mass to 34 parts by mass, the amount of spherical magnetic powder a (Epson Atmix Corporation "AW2-08PF3") used was changed from 39 parts by mass to 26 parts by mass, the amount of spherical magnetic powder b (Powdertech Corporation "M001") used was changed from 39 parts by mass to 26 parts by mass, and the amount of epoxy resin (Nippon Steel Sumikin Chemical Co., Ltd. "ZX-1059") used was changed from 13 parts by mass to 7 parts by mass. The resin composition was prepared in the same manner as in Example 1, except that the amount of curing accelerator b was changed to 1 part by mass, 1 part by mass of curing accelerator b ("2MZA-PW" manufactured by Shikoku Kasei Co., Ltd., an imidazole curing accelerator) was used instead of 0.1 part by mass of curing accelerator a ("TBP-DA" manufactured by Hokko Chemical Industry Co., Ltd.), 14 parts by mass of phenolic resin ("LA-7054" manufactured by DIC Corporation) was not used, and 12 parts by mass of phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation) was not used.
[0218] <Example 6> The amount of spherical magnetic powder a (Epson Atmix's "AW2-08PF3") used was changed from 39 parts by mass to 38 parts by mass, the amount of spherical magnetic powder b (Powder Tech's "M001") used was changed from 39 parts by mass to 38 parts by mass, the amount of epoxy resin (Nippon Steel Sumikin Chemical's "ZX-1059") used was changed from 13 parts by mass to 7 parts by mass, 1 part by mass of curing accelerator b (Shikoku Kasei's "2MZA-PW", imidazole curing accelerator) was used instead of 0.1 part by mass of curing accelerator a (Hokkaido Chemical Industry's "TBP-DA"), 14 parts by mass of phenolic resin (DIC's "LA-7054") was not used, and 12 parts by mass of phenoxy resin (Mitsubishi Chemical's "YX7553BH30") was not used. Except for this, the resin composition was prepared in the same manner as in Example 1.
[0219] <Example 7> The amount of flat magnetic powder a (Sanyo Special Steel Co., Ltd.'s "PST-4") used was changed from 50 parts by mass to 40 parts by mass, the amount of spherical magnetic powder a (Epson Atmix Corporation's "AW2-08PF3") used was changed from 39 parts by mass to 20 parts by mass, the amount of epoxy resin (Nippon Steel Sumikin Chemical Co., Ltd.'s "ZX-1059") used was changed from 13 parts by mass to 5 parts by mass, and 0.1 parts by mass of hardening accelerator a (Hokuko Chemical Industry Co., Ltd.'s "TBP-DA") was replaced with 0.1 part by mass of hardening accelerator b (Shikoku Kasei Co., Ltd.'s "2MZA-PW", imidazole-based hardening accelerator). A resin composition was prepared in the same manner as in Example 1, except that 0.4 parts by mass of toluene was used, 2 parts by mass of a dispersant (NOF Corporation, polyoxyalkylene dispersant "SC-1015F"), and 2 parts by mass of a cyclic ketone solvent (Junsei Chemical Co., Ltd., "Cyclohexanone") were further added, 39 parts by mass of spherical magnetic powder b (Powder Tech Co., Ltd., "M001") was not used, 14 parts by mass of phenolic resin (DIC Corporation, "LA-7054") was not used, and 12 parts by mass of phenoxy resin (Mitsubishi Chemical Corporation, "YX7553BH30") was not used.
[0220] <Comparative Example 1> The amount of flat magnetic powder a (Sanyo Special Steel Co., Ltd. "PST-4") used was changed from 50 parts by mass to 55 parts by mass, the amount of epoxy resin (Nippon Steel Sumikin Chemical Co., Ltd. "ZX-1059") used was changed from 13 parts by mass to 3 parts by mass, the amount of phenolic resin (DIC Corporation "LA-7054") used was changed from 14 parts by mass to 4 parts by mass, the amount of phenoxy resin (Mitsubishi Chemical Corporation "YX7553BH30") used was changed from 12 parts by mass to 3 parts by mass, 39 parts by mass of spherical magnetic powder a (Epson Atomics Corporation "AW2-08PF3") was not used, and 39 parts by mass of spherical magnetic powder b (Powder Tech Co., Ltd. "M001") was not used. Except for this, the resin composition was prepared in the same manner as in Example 1.
[0221] <Comparative Example 2> The amount of spherical magnetic powder a (Epson Atmix's "AW2-08PF3") was changed from 39 parts by mass to 65 parts by mass, the amount of epoxy resin (Nippon Steel Sumikin Chemical's "ZX-1059") was changed from 13 parts by mass to 3 parts by mass, the amount of phenolic resin (DIC's "LA-7054") was changed from 14 parts by mass to 4 parts by mass, the amount of phenoxy resin (Mitsubishi Chemical's "YX7553BH30") was changed from 12 parts by mass to 3 parts by mass, 2 parts by mass of cyclic ketone solvent (Junsei Chemical's "Cyclohexanone") was further added, 50 parts by mass of flat magnetic powder a (Sanyo Special Steel's "PST-4") was not used, and 39 parts by mass of spherical magnetic powder b (Powder Tech's "M001") was not used. Except for this, the resin composition was prepared in the same manner as in Example 1.
[0222] <Calculation of aspect ratio> In the observation by the scanning electron microscope, 50 magnetic powder particles were randomly selected, the length of the longest line segment connecting the two longest points on the outline of the particle in plan view was measured, and the average major axis length was calculated from the average value (number average). The magnetic powder was embedded in a polyester resin (JP-21111001, unsaturated polyester, manufactured by Marumoto Struers) and cured at 80°C for 30 minutes, and then polished (SiC-polishing paper #4000, manufactured by Struers) using a polishing and grinding machine (STRUERS-S5629B, manufactured by Struers), and the polished surface was observed by the scanning electron microscope. For 50 particles randomly selected from the magnetic powder, the thickness Y in the thickness direction of the magnetic powder was measured based on the scanning electron microscope image, and the average thickness ((Ym+Yn) / 2) was calculated from the maximum value Ym and the minimum value Yn, and further, the flattening ratio (average major axis length / average thickness) was calculated.
[0223] <Aspect ratio calculation> In the observation by the scanning electron microscope, 50 magnetic powders were randomly selected, and the length of the longest line segment connecting the two longest points on the outline of the particle in a plan view was measured, and the average major axis length was calculated from the average value (number average). At the same time, the length of the short side of a rectangle with the minimum area that circumscribes the outline of the particle and has a long side parallel to the longest line segment was measured, and the average minor axis length was calculated from the average value. The aspect ratio was calculated based on the value obtained by dividing the average major axis length by the average minor axis length.
[0224] <10% particle size (D 10 ), average particle size (D 50 ), and 90% particle size (D 90 ) calculation> The magnetic powder was dispersed in pure water using ultrasonic waves to prepare a measurement sample. The particle size distribution of the magnetic powder was measured on a volume basis using a laser diffraction scattering type particle size distribution measuring device (HORIBA, Ltd., "LA-960") to obtain the 10% particle size (D 10 ), 50% particle size (average particle size) (D 50 ), and 90% particle size (D 90 ) was calculated.
[0225] <Test Example 1: Evaluation of Paste and Film Formation> The fluidity of the resin compositions prepared in the examples and comparative examples was confirmed, and the resin compositions of Examples 1 to 7 and Comparative Example 2, which were in a paste form with coatability, were made into films. A polyethylene terephthalate (PET) film ("PET501010" manufactured by Lintec Corporation, thickness 50 μm) treated with a silicone-based release agent was prepared as a support. Each resin composition was uniformly applied onto the release surface of the PET film with a doctor blade so that the thickness of the resin composition layer after drying was 100 μm, to obtain a resin sheet. The resin composition was evaluated for its paste and film formation according to the following evaluation criteria.
[0226] (Evaluation criteria for pasting) "Good": Paste-like with good fluidity and good coatability. "X": No fluidity, coating not possible.
[0227] (Filming evaluation criteria) "Good": No holes and the film thickness is uniform. "X": Holes were formed and the film thickness was non-uniform, or the film had no fluidity and could not be made into a film.
[0228] <Test Example 2: Measurement and Evaluation of Relative Permeability> The resin sheet obtained in Test Example 1 was heated at 190°C for 90 minutes to heat-cure the resin composition layer, and the support was peeled off to obtain a sheet-like cured product. The obtained cured product was cut into a test piece having a width of 5 mm and a length of 18 mm to be used as an evaluation sample. The evaluation sample was measured for relative permeability (μ') at room temperature of 23°C using an Agilent Technologies ("HP8362B" manufactured by Agilent Technologies) at a measurement frequency of 10 MHz by a 3-turn coil method. The relative permeability was evaluated according to the following evaluation criteria.
[0229] (Evaluation criteria for relative permeability) "Good": Relative permeability is 11 or more. "X": Relative permeability is less than 11. "Not specified": Unable to be filmed and therefore unable to measure.
[0230] <Test Example 3: Viscosity Measurement> Of the resin compositions obtained in the examples and comparative examples, the resin compositions of Examples 1 to 7 and Comparative Example 2, which were in a paste state, were subjected to viscosity measurements (Pa s) using an E-type viscometer (Toki Sangyo Co., Ltd. "RE-80U", 3°×R9.7 cone, rotation speed 5 rpm) while maintaining the temperature at 25±2°C.
[0231] The non-volatile components and their contents in the resin compositions of the Examples and Comparative Examples, as well as the measurement results and evaluation results of the Test Examples, are shown in Table 1 below.
[0232] [Table 1]
[0233] From the above, it has been found that by using a resin composition containing (A) a magnetic powder and (B) a thermosetting resin, in which component (A) contains (A-1) a flat magnetic powder and (A-2) a spherical magnetic powder, and the average minor axis length of the flat magnetic powder (A-1) is 1 μm or more, it is possible to obtain a magnetic material that is easy to form into a paste or film and has excellent relative magnetic permeability. [Explanation of symbols]
[0234] 10 Core Board 11 Support substrate 12 1st metal layer 13 Second metal layer 14 through hole 20 Plating layer 30a Resin composition 30 Cured product 40 Conductor Layer 41 Patterned conductor layer 100 Circuit Board 200 Inner layer board 200a 1st main surface 200b 2nd main surface 220 through hole 220a Through hole wiring 240 External terminal 300 Magnetic part 310 Resin sheet 320a Resin composition layer 320 1st cured material layer 330 Support 340 Second cured layer 360 Beer Hall 360a via hole wiring 400 Coil-shaped conductive structure 420 First conductor layer 420a Land 440 Second conductor layer
Claims
1. A resin composition comprising (A) a magnetic powder and (B) a thermosetting resin, The component (A) includes (A-1) flat magnetic powder and (A-2) spherical magnetic powder, The average minor axis length of the component (A-1) is 1 μm or more, A resin composition, wherein the content of the component (A-1) is 30% by mass to 80% by mass, based on 100% by mass of the non-volatile components in the resin composition.
2. The resin composition according to claim 1, wherein the aspect ratio of the component (A-1) is 2 or more, and the aspect ratio of the component (A-2) is less than 2.
3. The resin composition according to claim 1 or 2, wherein the average particle size of the component (A-1) is 10 μm to 100 μm.
4. The resin composition according to any one of claims 1 to 3, wherein the average particle size of the component (A-2) is 0.1 µm to 40 µm.
5. The resin composition according to any one of claims 1 to 4, wherein the mass ratio of the component (A-1) to the component (A-2) (component (A-1) / component (A-2)) is 0.4 to 2.
3.
6. The resin composition according to any one of claims 1 to 5, wherein the content of the component (A) is 25 volume% to 75 volume% when the non-volatile components in the resin composition are 100 volume%.
7. The resin composition according to any one of claims 1 to 6, wherein the content of the component (A) is 70% by mass to 96% by mass, based on 100% by mass of non-volatile components in the resin composition.
8. The resin composition according to any one of claims 1 to 7, wherein the component (B) comprises an epoxy resin (B-1).
9. The resin composition according to any one of claims 1 to 8, further comprising (C) a curing accelerator.
10. The resin composition according to any one of claims 1 to 9, wherein the cured product of the resin composition has a relative magnetic permeability (μ') of 11 or more when measured at a measurement frequency of 10 MHz and 23°C.
11. The resin composition according to any one of claims 1 to 10, having a viscosity at 25°C of 0.05 Pa·s to 1500 Pa·s.
12. A resin sheet comprising a support and a resin composition layer formed from the resin composition according to any one of claims 1 to 11 provided on the support.
13. A cured product of the resin composition according to any one of claims 1 to 11.
14. A circuit board comprising: a substrate having a through hole; and a cured product of the resin composition according to any one of claims 1 to 11 filled in the through hole.
15. A circuit board comprising a cured layer which is a cured product of the resin composition according to any one of claims 1 to 11.
16. An inductor substrate comprising the circuit board according to claim 14 or 15.
Citation Information
Patent Citations
Resin composition for dust core, dust core, reactor, and electric device
JP1997102409A
Package for semiconductor device
JP2002110863A
Epoxy resin composition and electromagnetic wave shielding / absorbing material using the same
JP2002234988A
Magnetic loss material and filter circuit using it
JP2003158003A
Soft magnetic particle powder, soft magnetic resin composition, soft magnetic film, soft magnetic film laminate circuit board and position detector
JP2015092543A
